(untitled) (Ustozlar uchun, 2025)
This article explores the ethical and legal challenges arising from the growing autonomy of artificial intelligence (AI) systems. It examines the problem of accountability when AI errors lead to harm or social consequences, highlighting the ambiguity of assigning responsibility between developers, users, and autonomous algorithms. Examples from healthcare, transportation, and digital platforms are analyzed to demonstrate the complexity of ethical evaluation. The author concludes that the key to responsible AI lies in transparency, shared accountability, and the preservation of human oversight in all critical decision-making processes.